2018
DOI: 10.1093/nar/gky030
|View full text |Cite
|
Sign up to set email alerts
|

Direct transfection of clonal organoids in Matrigel microbeads: a promising approach toward organoid-based genetic screens

Abstract: Organoid cultures in 3D matrices are relevant models to mimic the complex in vivo environment that supports cell physiological and pathological behaviors. For instance, 3D epithelial organoids recapitulate numerous features of glandular tissues including the development of fully differentiated acini that maintain apico-basal polarity with hollow lumen. Effective genetic engineering in organoids would bring new insights in organogenesis and carcinogenesis. However, direct 3D transfection on already formed organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…Protein-based hydrogels including collagen, fibrin, and Matrigel ® , as natural extracellular matrices (ECM) analogues, have been widely investigated for various applications, like three-dimensional (3D) culture, tissue engineering, and regenerative medicine, because they are biocompatible and have excellent innate bioactive properties such as enzyme degradation and good control over cellular activities (adhesion, proliferation, migration, and differentiation) 14 . Matrigel ® is one of the most popular protein-based hydrogels 57 . Matrigel ® is a gelatinous protein mixture derived from Engelbreth-Holm-Swarm mouse sarcoma tumors and contains mainly proteins (laminin, type IV collagen, and entactin) and a small portion of proteoglycans and growth factors 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Protein-based hydrogels including collagen, fibrin, and Matrigel ® , as natural extracellular matrices (ECM) analogues, have been widely investigated for various applications, like three-dimensional (3D) culture, tissue engineering, and regenerative medicine, because they are biocompatible and have excellent innate bioactive properties such as enzyme degradation and good control over cellular activities (adhesion, proliferation, migration, and differentiation) 14 . Matrigel ® is one of the most popular protein-based hydrogels 57 . Matrigel ® is a gelatinous protein mixture derived from Engelbreth-Holm-Swarm mouse sarcoma tumors and contains mainly proteins (laminin, type IV collagen, and entactin) and a small portion of proteoglycans and growth factors 5 .…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, in our experience, the use of micro-bioreactors significantly enhance the acquisition and maintenance of a high plasticity state, providing a useful platform in stem cell organoid technology for long-term culture of different cell types, ranging from epigenetically erased cells to embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs), as well as mesenchymal stem cells (MSCs) [ 65 ]. Interestingly, parallel studies also demonstrated that encapsulation systems can be successfully used to store and cryopreserve organoids without altering cell growth and differentiation ability, as well as to perform post-treatments, such as direct transfection, and post-genetic screen and organoid analysis [ 83 ].…”
Section: D Cell Culture Systemsmentioning
confidence: 99%
“…The third method involves direction delivery of Cas9 and sgRNA to the organoids without generating single cells ( Matano et al, 2015 ). Of the three methods, the first two have been employed more widely due to difficulties associated with efficient gene delivery through 3D matrices ( Laperrousaz et al, 2018 ). Since hydrogel matrices can often pose diffusional limitations to highly charged, relatively large non-viral gene delivery vectors, limitations remain in using CRISPR Cas9 to study organoids.…”
Section: Crispr Cas9 Systemsmentioning
confidence: 99%